پاکستانیت اور جمیل جالبی کی فکری اساس: Pakistaniism and the intellectual foundation of Jamil Jalibi - bano, Dr.fazeelat; Zaidi, Dr. Bazar; Anwar, Haris (Tashkeel e Jadeed, 2025)
Behind the veil of national identity lies an intellectual dimension in which the overall life of the people of any country or society is presented. Human customs, way of life, feelings and emotions, language, literature, religion and civilization are all integrated into one unit. Just as civilization resembles the flow of a continuously flowing river, the aesthetic values of culture play a special role in national identity. Immediately after the establishment of Pakistan, the need for national identity and Pakistan civilization was felt. Different thinkers and intellectuals have presented their views on the problem of identity in their own way. Dr. Jameel Jalbi was also one of those who dared to present the meaning of civilization and culture and national identity in its overall intellectual context. He presented the aesthetic attitudes of the structure of Pakistanies and the internal and external elements of the culture in his scenario. Among the problems faced by the nascent Pakistani society, autonomy, liberalism, common language, mental harmony and cultural factors along with the trend of newly emerging consciousness took a special shape. Dr. Jameel Jalbi has built the links of identity thanks to his insight and vision coordination.